Private pharmacy staff in Hanoi dispensing steroids - theory and practice - Larsson, Mattias (Centro de Investigaciones y Publicaciones Farmaceuticas, 2006)
OBJECTIVE: To investigate self reported practice and actual practice of private pharmacy staff in relation to drug regulations and provision of prednisolone (a prescription-only corticosteroid) on request to treat lower back pain. METHOD: Sixty private pharmacies in Hanoi were randomly selected. Self reported practice was assessed through interviews with pharmacy staff using a questionnaire; actual practice was assessed with the Simulated Client Method with 5 encounters in each pharmacy (a total of 295 encounters). RESULTS: Sixty percent of the pharmacy staff interviewed said that they would not dispense corticosteroids without prescription and 60% could mention some adverse effects. In practice all but one pharmacy dispensed corticosteroids without prescription in 76 % of all the encounters. Questions and advice given to the clients were associated with significantly lower dispensing of corticosteroids. CONCLUSION: The low compliance with prescription regulations and the discrepancy between stated practice and actual practice raises concerns. This study indicates that commercial pressures exceed the deterrent effect of current drug regulations and their implementation and hence enforcement of regulations needs to be improved.